Discontinuous deformation analysis for subsidence of fractured formations under seepage: a case study - Gao, Jingyao (2024)
With the growing prominence of recycling projects of groundwater, the attention towards subsidence concerns in geological formations is intensifying. However, due to the long evolutionary time and complex underground discontinuities, the deformation field and subsidence mechanism are difficult to obtain. To this concern, this study implemented the Hydro-Mechanical Coupled Discontinuous Deformation Analysis (HM-DDA) in a groundwater recycling project located at a goaf mining site. The method for establishing numerical stratigraphic models and determining the required numerical parameters is introduced. This contributes to the comprehensive reconstruction of changes in in-situ stress within the goaf area, encompassing the initial stress equilibrium state, as well as the processes of water pumping and injection. The results indicated that the water injection process mitigated stress concentrations at both ends of the goaf area. Specifically, a 30-m rise in water head resulted in a corresponding elevation of the ground surface by 3.94 ​cm.